THE UNHEALTHY EFFECTS OF BULLYING AMONGST SCHOOL CHILDREN - Biswas, Prarthita; Ganguly, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
Bullying is the most common type of violence among children and adolescents in school. Sometimes bullying can also come from the side of teachers in the school environment. There are some misconceptions about bullying, which should be cleared. Various researches have shown a good number of prevalence of school bullying worldwide. There are various causes of bullying, including psychological factors, family factors, school factors, socio- economic factors, and media. It affects both who are bullied, and who bully others, adversely. Along with them who witness this bullying also faces the impact. To address these problems some preventive measures can be followed properly.